Green-synthesized carbon dots from ginger: Multifunctional agents against oral pathogens with biocompatibility in human gingival fibroblast cells - Shaeesta Khaleelahmed Bhavikatti; Siti Lailatul Akmar Zainuddin; Rosmaliza Binti Ramli; Sameer J. Nadaf; Padma B. Dandge; Masidd Khalate; Mohmed Isaqali Karobari (Current Plant Biology)
Persistent antibiotic use in treating oral infections often leads to drug resistance in pathogenic bacteria, notably impacting conditions like periodontitis. Addressing this challenge, the study pioneers the use of carbon dots (CDs) synthesized from ginger rhizomes (Zingiber officinale) as a novel biocompatible material. CDs were synthesized via the hydrothermal method, emphasizing a green approach, and comprehensively characterized for their optical properties and structural uniformity. The synthesized CDs showed a zeta potential of −24.9 mV, confirming the formation of stable and well-dispersed particles. Dynamic Light Scattering (DLS) confirmed an average particle size of 2.9 nm, thus validating the formation of CDs. Biomedical assessments demonstrated that the synthesized CDs were non-cytotoxic to human gingival fibroblast cell lines, with effective free radical scavenging activity and high total antioxidant capacity, as indicated by their IC50 values. CDs also exhibited moderate inhibition of protein denaturation compared to the standard. Moreover, they showed significant inhibitory effects against bacterial strains (Pseudomonas aeruginosa, Lactobacillus acidophilus, Escherichia coli, Staphylococcus aureus) and fungal strains (Aspergillus niger, Candida albicans) at minimal concentrations. Notably, CDs inhibited the growth of periodontal pathogens including Aggregatibacter actinomycetemcomitans, Tannerella forsythia, Porphyromonas gingivalis, and Prevotella intermedia. These findings underscore the potential of CDs as multifunctional agents possessing anti-inflammatory, antifungal, antioxidant, and antibacterial properties. Remarkably, they offer a promising alternative to conventional antibiotics, potentially revolutionizing oral healthcare. Their proven biocompatibility and potent bioactivity underscore their innovative potential in biomedical research. Future studies should further assess their efficacy in vivo to fully harness their clinical potential.